Adsorption of the disinfectant benzalkonium chloride on montmorillonite: Synergistic effect in mixture of molecules with different chain lengths - Zanini, Graciela Pilar (2013)
The biocide benzalkonium chloride (BAC) is a mix of cationic alkylbenzyldimethylammonium surfactants having different alkyl chain lengths. A comparative study of adsorption on the phyllosilicate clay montmorillonite of two of these surfactants, with alkyl chains having respectively 12 C atoms (BAC-12) and 14 C atoms (BAC-14), and a mixture of both surfactants is presented in this work. Adsorption isotherms were performed for individual surfactants and for a 1:1 mixture BAC-12+BAC-14. The adsorption was investigated in an ample concentration range that covers almost seven orders of magnitude in concentrations (from 1 nM to 10 mM), range that includes environmentally relevant concentrations. Quantification of BAC was performed by HPLC–UV and LC–MS and the results were completed with powder X-Ray diffraction. The adsorption of both surfactants leads to adsorption isotherms with two well differentiated steps. The first step corresponds almost exclusively to a cation exchange process, and the binding constant is very similar for both surfactants. The second step of the isotherms is observed at higher concentrations and adsorption is mainly driven by lateral interactions between surfactant molecules. The binding constant of this step is larger for BAC-14 than for BAC-12. Adsorption from a BAC-12+BAC-14 mixture shows a synergistic behaviour, possibly due to a better packing arrangement in the interlayer. Calculations show that in natural systems silicate clays are major sorbents of BAC at low concentrations whereas binding to humic acid is predominant at high concentrations.